2015
DOI: 10.1111/cea.12517
|View full text |Cite
|
Sign up to set email alerts
|

Allergic disorders and socio‐economic status: a study of schoolchildren in an urban area of Makassar, Indonesia

Abstract: SummaryBackground In urban centres of developing countries, there is great variation in socioeconomic status (SES) and lifestyle; however, little information is available on allergic disorders in groups with high-or low-SES within the same urban area. Objective To determine the prevalence of allergic disorders and investigate risk factors related to them among high-and low-SES schoolchildren in Makassar, the capital city of South Sulawesi, Indonesia. Method This cross-sectional study was performed in 623 child… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 43 publications
0
18
0
Order By: Relevance
“…Two major explanations are proposed: a delay in consultation and lower adherence to treatments. Conversely, atopic diseases seem to be more frequent in higher socioeconomic populations (37)(38)(39), but adherence to treatments is altered by low socioeconomic status (23)(24)(25). Herein we have shown that patients with psoriasis have the same socioeconomic inequalities as those with various other skin and non-skin-related diseases.…”
Section: Discussionmentioning
confidence: 71%
“…Two major explanations are proposed: a delay in consultation and lower adherence to treatments. Conversely, atopic diseases seem to be more frequent in higher socioeconomic populations (37)(38)(39), but adherence to treatments is altered by low socioeconomic status (23)(24)(25). Herein we have shown that patients with psoriasis have the same socioeconomic inequalities as those with various other skin and non-skin-related diseases.…”
Section: Discussionmentioning
confidence: 71%
“…It has been reported that this increase of eczema in developing countries could be caused by the rapid urbanization [8]. In line with this theory, eczema has been proven to be positively associated with urban and industrialized settings [9,10], obesity [11], higher socioeconomic status [12], smaller family size [13], and being free of helminth infections [14,15]. This theory is consistent with the Hygiene Hypothesis, which states that limited exposure to microorganisms in industrialized countries due to improved sanitary conditions, would increase immune reactivity.…”
Section: Introductionmentioning
confidence: 87%
“…93,101,102 This has been attributed partly to geohelminths, but the role of other infections and microbiome deserves investigation.…”
Section: Worms and Allergy-related Diseasementioning
confidence: 99%